External Egg Traits in Japanese Quail Vary by Maturity Age: Ciri-ciri Telur Luar pada Burung Puyuh Jepang Bervariasi Berdasarkan Usia Kedewasaan - Omer, Esam Saeed; Sidiq, Rawezh Dlshad; Shaker, Ahmed Sami (Academia Open, 2025)
General background: Egg traits are crucial indicators in poultry science due to their relevance to hatchability, chick survival, and consumer preferences. Specific background: While various factors influence egg quality, the impact of sexual maturity timing on external egg characteristics in Japanese quail remains underexplored. Knowledge gap: Limited studies have investigated how variations in the onset age of sexual maturity directly affect measurable external egg traits. Aims: This study aimed to assess the effects of early and late sexual maturity on external egg quality in Japanese quail. Results: Using 682 eggs categorized into four sexual maturity classes, we found that the age of sexual maturity significantly influenced egg weight, length, surface area, and volume, while body weight, egg breadth, and shape index remained unaffected. Novelty: The findings establish that earlier sexual maturity is associated with larger eggs, highlighting physiological advantages during early reproductive phases. Implications: These results offer insights for breeding strategies aiming to enhance egg production and quality by selecting optimal maturity ages, thus improving both economic outcomes and biological efficiency in quail production systems. Highlight : The age of sexual maturity significantly affects egg weight, length, surface area, and volume in Japanese quail. Delayed maturity results in lower egg mass and size, indicating suboptimal reproductive performance. Strong correlations between egg surface area and volume highlight key structural traits for selection programs. Keywords : Sexual Maturity, Japanese Quail, Egg Traits, Egg Quality, External Characteristics